Understanding interpretations of credibility, health literacy and health information seeking in Black and South Asian ethnic communities in the United Kingdom: A qualitative study - Tushna Vandrevala; Kristin Hanson; Celayne Heaton-Shrestha; Richard Boulton; Lindsay M. Bearne (PLOS One, 2026)
Health literacy is essential for making informed healthcare decisions, yet ethnic minority communities often face disparities due to limited access to culturally relevant information. This qualitative study explores how South Asian and Black communities in the United Kingdom (UK) assess health information credibility, examining cultural influences and expectations. Sixty-eight participants (42 South Asian, 26 Black) were recruited using purposive sampling; data collection involved semi-structured interviews (n = 30) and community observations (n = 38). Findings revealed that cultural expectations shape perceptions of healthcare professionals and health information sources. Trusted sources included personal contacts and social media. Health information lacking personal or culturally relevant content led participants to seek alternative sources. While some credibility-seeking behaviours overlap with those observed in the general population, the unique social, cultural, and historical experiences of these populations shape how and why such behaviours are enacted, resulting in distinct patterns of trust and information use. Providers must recognise these dynamics to create personalised, culturally sensitive resources that enhance trust, health literacy, and equity. Tailored approaches, including trusted intermediaries and relevant communication channels, are crucial, while digital platforms must address misinformation.